IS THE FASHION STORE, PT MATAHARI DEPARTMENT STORE TBK STILL PROFITABLE IN THE ERA OF DIGITAL INNOVATION? For the Period of 2008-2017 - Daryanto, Wiwiek Mardawiyah; Brazer, Fransiscus X John; Alif, Jodipati (Emerging Markets : Business and Management Studies Journal, 2019)
Retail industry in Indonesia has grown rapidly alongside with the current growing of technology. By the ever-growing technology development, the behaviors of Indonesian people are also slightly changes to become more efficient and simple way of buying things. The study sought to observe the performance of PT Matahari Department Store Tbk (MDS) before and after the digital innovation that took place in the early 2010s. The aim of this study was to investigate whether the advent of E-commerce has affected PT MDS’s performance. Financial ratio such as profitability and overall measures were used to analyze PT MDS’s financial performance. Period taken in this study were in before (2008-2010) and after the appearance of E-Commerce in retail industry (2011-2017). This study found that in 2008-2010 (E-commerce first pilot project) the profitability performance of PT MDS was not in good condition. However, in 2011 or E-Commerce Emergence & Transition, PT MDS began to improve its financial performance by successfully recording positive trends in all financial ratios except ROE. This has occurred due to the impact of reverse stock and corporate restructuring in 2009. Additionally, an increase in the shareholding of public ownership was also taken in action in 2013 to drive up the price of company’s shares and boost the company's ratio. Thus, it can be sum up that PT MDS’s financial performance was not affected by the presence of E-commerce, instead it influenced by company’s actions. However, with an objective to adapt in this era, PT MDS has launched Matahari.com for targeting other segments and other strategies to keep up the improvements.